PENGARUH KOMPETENSI DAN KOMUNIKASI TERHADAP KINERJA GURU DENGAN KOMITMEN SEBAGAI VARIABEL INTERVENING DI SMA NEGERI 1 KEJAYAN KABUPATEN PASURUAN - Suciati, Bawuk (MAP (Jurnal Manajemen dan Administrasi Publik), 2024)
This study aims to test and analyze the influence of competence and communication with commitment as an intervening variable on teacher performance at SMA Negeri 1 Kejayan, Pasuruan Regency. The research was conducted at SMA Negeri 1 Kejayan, Pasuruan Regency with a sample of 60 teachers with a saturated sampling method, which is to make the entire population as a sample. Data collection was carried out by distributing questionnaires to teachers. The data was analyzed using quantitative descriptive analysis with partial least square. Based on the results of the analysis, the sample of this study found that competence had a positive but not significant effect on teacher performance and commitment; communication had a positive but not significant effect on teacher performance but had a significant positive effect on commitment; while commitment had a significant negative effect on teacher performance. Meanwhile, the commitment to mediate the influence of competence and communication mediating negatively is not significant to teacher performance.